1992
DOI: 10.1177/00220345920710031201
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme Enhances the Inhibitory Effects of the Peroxidase System on Glucose Metabolism of Streptococcus mutans

Abstract: The combined effect ofthe salivary peroxidase system and lysozyme on the glucose uptake of Streptococcus mutans NCTC 10449 was investigated. The bacteria were grown to late-exponential phase, washed, re-suspended in buffer at pH 6, and incubated with (1) 50 pg/ mL lysozyme from human milk for 60 min; (2) 7-15 gmol/L hypothiocyanous acid/hypothiocyanite for 10 min; and (3) lysozyme for 60 min prior to addition ofand incubation with hypothiocyanous acid/hypothiocyanite for 10 min. Glucose uptake was initiated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 48 publications
2
17
0
1
Order By: Relevance
“…This is in accordance with previous studies of the same S.mutans strain and human LZ Tenovuo, 1991: Wang andGermaine, 1991;Lenander-Lumikari et al, 1992], in dicating no bactericidal effect of LZ against this strain. Thus, it is most likely that the observed inhibition of the adherence of S.mutans to saliva-coated apatite was due to LZ, but not because o f any cell lysis induced by this en zyme.…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with previous studies of the same S.mutans strain and human LZ Tenovuo, 1991: Wang andGermaine, 1991;Lenander-Lumikari et al, 1992], in dicating no bactericidal effect of LZ against this strain. Thus, it is most likely that the observed inhibition of the adherence of S.mutans to saliva-coated apatite was due to LZ, but not because o f any cell lysis induced by this en zyme.…”
Section: Discussionsupporting
confidence: 93%
“…Physiological concentrations of (pseudo)halides and peroxidases were used. Previous studies on A. actinomycetemcomitans and S. mutans have shown that these halide concentrations, in combination with LP/MP and H 2 O 2 , cause signi®cant antibacterial effect [10,14], and that the peroxidase activities rapidly produce OSCN À from SCN À in the presence of H 2 O 2 [33]. H 2 O 2 concentration is not measurable in saliva, because it is actively produced and depleted in biochemical reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Many salivary proteins interact in vitro in ways that affect their joint interaction with oral bacteria. Lactoferrin, slgA, and lysozyme all may increase inhibitory effects of peroxidase (Tenovuo et al, 1982;Lenander-Lumikari et al, 1992a), and slgA against bacterial iron-binding proteins may enhance bacteriostatic iron-sequestration by lactoferrin (Ellison et al, 1988). On the other hand, bactericidal actions of lactoferrin can be blocked or enhanced by slgA specific to particular species (Lassiter et al, 1987;Motley and Arnold, 1987).…”
Section: (D) Protein Interactionsmentioning
confidence: 99%